CONSERVING WATER THROUGH SCIENCE AND TRADITION(A CASE STUDY FOR SOLAPUR) - Prof. Mr. Prashant Swami; Ms. Dhanashri Alure (International Journal of Innovations in Engineering Research and Technology, 2021)
Indian tourism is essentially driven by temple cities. Among these various ancient temple towns & cities, Solapur is not only important but also unique. The project of ‘Suvarna Solapur’ is recent launched which will attract maximum numbers of tourists in the coming year According to the Department of Tourism, in 2015 solapur temple attracts the maximum number of tourists’ visiting South India a phenomenal 2.5 crore people. This number is bound to increase in the future threatening the fragile eco-system. Hence there is a need to develop a holistic & sustainable model for a green tourism as well as pilgrimage experience. The mission for green solapur has a three dimensional approach:1.Discovering Linkages 2.Reviving Relations 3.Creating Nodes and Networks